Cost‐Effectiveness of Dopamine Agonists and Monoamine Oxidase B Inhibitors in Early Parkinson's Disease. Issue 9 (7th May 2021) - McIntosh, Emma; Kent, Seamus; Gray, Alastair; Clarke, Carl E.; Williams, Adrian; Jenkinson, Crispin; Ives, Natalie; Patel, Smitaa; Rick, Caroline; Wheatley, Keith; Gray, Richard; ,
ABSTRACT: Background: The PD MED study reported small but persistent benefits in patient‐rated mobility scores and quality of life from initiating therapy with levodopa compared with levodopa‐sparing therapies in early Parkinson's disease (PD). Objectives: The objective was to estimate the cost‐effectiveness of levodopa‐sparing therapy (dopamine agonists or monoamine oxidase type B inhibitors compared with levodopa alone. Methods: PD MED is a pragmatic, open‐label randomized, controlled trial in which patients newly diagnosed with PD were randomly assigned between levodopa‐sparing therapy (dopamine agonists or monoamine oxidase type B inhibitors ) and levodopa alone. Mean quality‐adjusted life‐years and costs were calculated for each participant. Differences in mean quality‐adjusted life‐years and costs between levodopa and levodopa‐sparing therapies and between dopamine agonists and monoamine oxidase type B inhibitors were estimated using linear regression. Results: Over a mean observation period of 4 years, levodopa was associated with significantly higher quality‐adjusted life‐years (difference, 0.18; 95% CI, 0.05–0.30; P  < 0.01) and lower mean costs (£3390; £2671–£4109; P  < 0.01) than levodopa‐sparing therapies, the difference in costs driven by the higher costs of levodopa‐sparing therapies. There were no significant differences in the costs of inpatient, social care, and institutional care between arms. There was no significant difference in quality‐adjusted life‐years between those allocated dopamine agonists and monoamine oxidase type B inhibitors (0.02; −0.17 to 0.13 in favor of dopamine agonists; P  = 0.81); however costs were significantly lower for those allocated monoamine oxidase type B inhibitors (£2321; £1628–£3015; P  < 0.01) because of the higher costs of dopamine agonists. There were no significant differences between arms for other costs. Conclusions: Initial treatment with levodopa is highly cost‐effective compared with levodopa‐sparing therapies. Monoamine oxidase type B inhibitors, as initial levodopa‐sparing therapy was more cost‐effective, with similar quality‐adjusted life‐years but lower costs than dopamine agonists. © 2021 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society